Future of Waste Management in the Czech Republic - Brix, Vojtěch (2019)
In this work the author identifies the potential of the Czech Republic to improve its waste management model. Regulatory push from the side of the European union for reduction of landfilling to up 10% (Czechia currently landfills about 50%) of generated waste creates opportunity to develop best in class sustainable waste management model. It would require adopting the modern technologies which has been developed for each step in waste processing hierarchy. Between European countries have been identified 3 approaches to waste management in compliance with the regulation– in Finland focusing on recovery, in Slovenia focusing on recycling and in Germany which is mixed strategy. Most suitable for Czech conditions is Finnish one which is also the most economical one. It would cost all stakeholders approximately 13-23 billion CZK to implement it and the result would be decrease in ecological footprint by 12-14%. Most ecological would be to focus on similar-to-Slovenia model which would costs about 33.5 billion CZK but deliver results of 31% ecological improvement in comparison to baseline (AS-IS status) scenario.